Critical review of biochemical pathways to transformation of waste and biomass into bioenergy. (March 2023) - Manikandan, Sivasubramanian; Vickram, Sundaram; Sirohi, Ranjna; Subbaiya, Ramasamy; Krishnan, Radhakrishnan Yedhu; Karmegam, Natchimuthu; Sumathijones, C.; Rajagopal, Rajinikanth; Chang, Soon Woong; Ravindran, Balasubramani; Awasthi, Mukesh Kumar
Graphical abstract: Highlights: Firewood biomass has traditionally been used to generate energy by burning. Pathways to anaerobic digestion, enzyme hydrolysis and microbial fuel cells were analyzed. Circular economy preserves the value of its by-products by reducing time. Anaerobic digestion and microbial fuel cells help to achieve biomass use with sustainability. Alternative fuels raise the demand for energy throughout the world. Abstract: In recent years, biofuel or biogas have become the primary source of bio-energy, providing an alternative to conventionally used energy that can meet the growing energy demand for people all over the world while reducing greenhouse gas emissions. Enzyme hydrolysis in bioethanol production is a critical step in obtaining sugars fermented during the final fermentation process. More efficient enzymes are being researched to provide a more cost-effective technique during enzymatic hydrolysis. The exploitation of microbial catabolic biochemical reactions to produce electric energy can be used for complex renewable biomasses and organic wastes in microbial fuel cells. In hydrolysis methods, a variety of diverse enzyme strategies are used to promote efficient bioethanol production from various lignocellulosic biomasses like agricultural wastes, wood feedstocks, and sea algae. This paper investigates the most recent enzyme hydrolysis pathways, microbial fermentation, microbial fuel cells, and anaerobic digestion in the manufacture of bioethanol/bioenergy from lignocellulose biomass.